emathematics.net
Español
User: desconectar
 
Maths Exercices
Subtraction of polynomials
Subtraction of polynomials.
Subtraction of two algebraic expressions is achieved by changing the sign of every term in the expression which is being subtracted and adding this result to the other expression.

Subtract Q(x) = 2y3+ 6 from P(x)= 30y3 - 29y2 - 3y
It is the same as simplify: (30y3 - 29y2 - 3y)-(2y3+ 6)
Solution: P(x) - Q(x)= 28y3 - 29y2 - 3y - 6

Note the following combinations:
30y3 - 2y3 = 28y3


Solution:   x5 x4 x3 x2 x